Síntese de controladores misto H2/H [infinito] para sistemas de controle via rede - Pauli, Renata Baraldi de (2017)
The problem addressed in this work is a Networked Control System (NCS) design for linear parameter varying (LPV) systems, considering that both the input signal and states variables are subject to delays inherent to the network. This work proposes the use of a robust stabilization method based on the Lyapunov-Krasovskii functional, using a mixed H2/H∞ control technique, which relies on the resolution of a set of Linear Matrix Inequalities (LMIs) conditions. To this end, it is developed a synthesis condition for the H2 controller and, for the H∞ controller, conditions established in the literature are used. The LMI problem is solved in a polytopical way, considering that the variables are polynomially dependent of parameters, being the polynomials of arbitrary degree. The effectiveness of the technique is illustrated by a numerical experiment, comparing the results obtained with the mixed control, H∞ control and H2 control.